Iron-deficiency anemia – often a clinical challenge (Indian Journal of Case Reports, 2025)
Celiac disease (CD) is an autoimmune disorder of the small intestine that has a wide array of systemic manifestations. Despite its rising prevalence, CD continues to be underdiagnosed. An 11-year-old male child presented with a history of itchy skin rash, failure to gain height, occasional diarrhea, pica, and lethargy. On physical examination, signs of anemia were present. Our patient had been repeatedly dewormed and given iron, folic acid, and vitamin B12 supplementation in the past. Clinical evaluation, serological evidence, and blood parameters raised a strong suspicion of CD. This was confirmed with a duodenal biopsy. A gluten-free diet was initiated as part of the treatment, and resolution of symptoms was observed. Our case is a stark reminder that malabsorption syndromes – particularly CD – can masquerade behind extraintestinal manifestations even in the absence of gastrointestinal complaints. Keeping CD in the differential whenever unexplained systemic signs appear allows clinicians to diagnose early and start timely management.